Student Learning through Project-based Learning of Motion Capture Techniques Course - Phunsa, Asst. Prof. Suwichai (Journal for Developing the Social and Community, 2018)
This aim of the research are 1) to study of student learning through projectbased learning (PjBL) of motion capture techniques course and 2) to study the opinions of 34 students. The sample selection using a purposive sampling and the instructional management and assessment of learners' learning achievement through the five-step learning management project. Research tools include satisfaction evaluation form, survey online, and Statistics in the research included mean, standard deviation and ttest (independent samples). The results showed that; The learning outcomes of the learners are met by 4 teams and are at the moderate level. Five items of satisfaction in each area, including 20 items include the teaching and learning, Learning content, Presentation, and the learning media. Overall satisfaction was high the mean was (  = 3.78, S.D. = 0.38). The opinions of the online survey including 15 items, Overall satisfaction was high the mean was (  = 3.93, S.D. = 0.84) finally, the analysis compares the levels of opinion and acceptance with different sex, the level of opinion was not different statistically significant at the 0.05 level.